2011
DOI: 10.1258/phleb.2010.010050
|View full text |Cite
|
Sign up to set email alerts
|

Handlebar injury to femoral vein: case report and review

Abstract: Handlebar injury varies from minor trauma to life-threatening visceral and vascular damage resulting in a significant morbidity among children. Femoral vein injuries secondary to handlebar trauma are rare but potentially serious. Venous continuity should be restored and several techniques for repair of femoral injuries have been described. We reported a case of femoral vein injury secondary to handlebar trauma in a child and we described techniques used for its repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Case reports of extremity vascular injuries exist; but within our cohort, vascular injury represents 3.7% of handlebar injuries and should be considered in any patient with the concern of a handlebar injury to the extremity. [14][15][16] Soft tissue injuries were more frequent in patients with handlebar injuries, but the incidence of requiring intervention was no different across groups. Within the handlebar group, 4 patients had an abdominal wall hernia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Case reports of extremity vascular injuries exist; but within our cohort, vascular injury represents 3.7% of handlebar injuries and should be considered in any patient with the concern of a handlebar injury to the extremity. [14][15][16] Soft tissue injuries were more frequent in patients with handlebar injuries, but the incidence of requiring intervention was no different across groups. Within the handlebar group, 4 patients had an abdominal wall hernia.…”
Section: Discussionmentioning
confidence: 97%
“…All of the nonhandlebar injuries were fractures, many of which were treated operatively the day after admission, whereas the handlebar injuries included 4 vascular injuries, which were taken emergently/urgently for surgical repair. Case reports of extremity vascular injuries exist; but within our cohort, vascular injury represents 3.7% of handlebar injuries and should be considered in any patient with the concern of a handlebar injury to the extremity 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…While rare in occurrence, most vascular traumas associated with this mechanism of injury involve the common femoral artery (CFA) or external iliac artery (EIA) 9. To our knowledge, venous trauma stemming from handlebar trauma has only been reported three times,10–12 and this is the first case report to feature a patient experiencing complete destruction to both the CFA and the CFV due to handlebar trauma. This is an uncommon mechanism of injury and is frequently missed on the initial presentation,9 with potentially catastrophic injuries if unattended.…”
Section: Introductionmentioning
confidence: 90%
“…But Yelon et al reported that 86% of patients treated by ligation of pelvic or lower extremity venous injuries were free of oedema at discharge 3 . Thrombosis and failure of repair can occur in up to 15% patency rate up to 74% following repair 4 . For optimal long-term patency and to minimize chronic complications a durable venous repair is needed.…”
Section: Dear Editormentioning
confidence: 99%